A comparison of preterm and full-term infant emotional regulation development through infant-mother affect synchrony - Low, Heather Yee Theng (Nanyang Technological University, 2024)
Emotional regulation aligns goal-directed behaviour towards optimal outcomes. An integral contribution towards developing emotional regulation is the establishment of synchronised affect during infant-mother interactions. With at-risk groups like preterm infants displaying greater vulnerability towards poorer emotional regulation outcomes, this study aimed to specifically compare preterm (N = 10) and full-term (N = 10) infant-mother dyads in measures of dyadic affect synchrony and their relations to infants emotional self-regulation. In this regard, dyadic interactions during a free play task and infant performance in a response inhibition task were analysed. Several findings were revealed: (1) preterm infants experienced highest positive affect in singing/dancing, but overall exhibited significantly lower positive affect than full-term infants, (2) compared to the full-term group, mothers of preterm infants made behavioural adjustments (i.e. reduced positive and negative affect), especially during tickling, and took on more responsive roles in dyadic interactions, (3) preterm infants whose mothers responded to their emotions during dyadic interactions had better emotional self-regulation. These findings suggested that effective modifications of maternal contingent responses to preterm infants could alleviate their predisposing vulnerabilities and facilitate similar patterns of emotional regulation as full-term infants. This highlights the significant role of sensitive maternal parenting in infant emotional regulation development.